IMPLEMENTASI METODE TALAQQI DALAM MENINGKATKAN HAFALAN AL-QUR’AN PADA ANAK USIA DINI (Studi Kualitatif di TK As Salam Bekasi Utara) - Farkhan Ar Robbani; Agus Suprianto (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
This study describes the implementation of the Talaqqi Method in Improving the Memorizing ofthe Qur’an in Early Childhood, which has been carried out at As Salam Kindergarten, North Bekasi.The aims of this study were: (1) To identify and analyze the implementation of the talaqqi method inimproving the memorization of the Qur’an in early childhood. (2) To find out what factors supportand hinder the implementation of the talaqqi method in improving the memorization of the Qur’an inearly childhood. This research was conducted at As Salam Kindergarten, North Bekasi, this researchmethod uses naturalistic qualitative methods, with data collection procedures using observation,interviews, and documentation studies. This data analysis is carried out qualitatively by interpretingand describing holistically or logically, on the data received. The respondents in this study were theprincipal, teacher of memorizing the Qur’an and guardians of As Salam Kindergarten students. ResultsThis study shows that the implementation of the Talaqqi Method in improving the memorization ofthe Qur’an in early childhood can run well according to the theory and steps in the implementationof the talaqqi method.It can be proven that students who previously had not been able to memorizethe Qur’an were able to memorize up to 1 juz of the Qur’an in approximately 1 year. So it can beconcluded that the implementation of the talaqqi method can improve the memorization of the Qur’anin early childhood. This is evident from the results of interviews with school principals who said thatthe talaqqi method can improve the memorization of the Qur’an. This can be seen from the value givenby the teacher of memorizing the Qur’an.